Corporate governance mechanisms with conventional bonds and Sukuk yield spreads - Mohd Saad N.; Haniff M.N.; Ali N. (Elsevier B.V., 2023)
The main objective of this study is twofold. First, is to investigate the significant mean difference between conventional bonds and sukuk yield spreads. Second, is to investigate the relationship between yield spreads and corporate governance mechanisms. The data covers from 2000 to 2014 for 256 and 405 tranches of long-term and medium-term issuances of conventional bonds and sukuk respectively. Unbalanced panel data are applied. The findings show that (1) there are significant mean different between yield spreads of conventional bonds and sukuk, and (2) the institutional ownerships and BOD characteristics, role duality and size significantly reduce yield spreads in long-term conventional bonds and sukuk. The institutional investors should have more shareholdings in the issuer firms, those who are issue long-term conventional bonds and medium-term sukuk since the default risk is low. BOD also need to fully compliant to Malaysian Code on Corporate Governance (MCCG) for best practices in the firm. 2019 The Authors